Potential Dietary Contributions from Rice and Wheat Flour Fortification in the Solomon Islands: Results from the 2012–2013 Household Income and Expenditure Survey (P10-048-19). (13th June 2019) - Pachon, Helena; Imhoff-Kunsch, Beth; Shakya, Iju; Namohunu, Salome Aroma Diatalau; Pitaboe, Anna; Wong, Pierre; Tsang, Becky; Codling, Karen; Foley, Jessica
Abstract: Objectives: Solomon Islands (SI) mandated wheat flour fortification in 2010. Rice is a key staple food in SI, and its fortification may provide an opportunity to deliver additional micronutrients to the population. The objective was to determine whether fortified rice (proposed) and fortified wheat flour potentially benefit women of reproductive age (WRA). Methods: We analyzed data from the 2012–2013 Household Income and Expenditure Survey to quantify food purchases, which served as a proxy for food consumption. We accounted for varied household composition by using adult male equivalent (AME) adjustments. Results: Among 4478 households, 95.6% purchased rice and 86.6% purchased at least 1 food containing fortified wheat flour in the previous 14 days. Median apparent intake of rice among WRA was 205 g/d/AME. If fortified according to proposed standards, this apparent intake could result in the consumption of 12.3 mg iron/d, fulfilling 44% of the estimated average requirement (EAR), and 226 µg folic acid/d, satisfying 57% of World Health Organization's recommended intake of 400 µg/d. Overall, apparent rice consumption could fulfill 113%, 114%, and 131% of the EAR for WRA for zinc, thiamin, and niacin, respectively. Fortified wheat flour was consumed in much lower quantities, with an estimated apparent median intake of 22 g/d/AME among WRA and 78 g/d/AME among women in urban populations. Conclusions: The potential benefit of fortified wheat flour in SI is likely limited to urban populations. Apparent consumption of fortified rice in SI could contribute considerably to daily intake of iron, B vitamins including folic acid, and zinc among WRA. Funding Sources: Department of Foreign Affairs and Trade under the Government of Australia.